A dentifrice containing salivary enzymes and xylitol exhibits superior antimicrobial activity in vitro against adherent Streptococcus mutans compared to a chlorhexidine dentifrice. - Moran, Gary (My University, 2023)
Human saliva contains natural antimicrobial enzymes. In this in-vitro study, we evaluate the antimicrobial activity of a dentifrice containing a salivary enzyme complex (SEC) with xylitol versus a standard 0.12% chlorhexidine (CHX) dentifrice. Adherent cells of Streptococcus gordonii, Strep. mutans, Actinomyces naeslundii, Fusobacterium nucleatum subsp polymorphum, and Corynebacterium matruchotii were exposed to SEC-xylitol and CHX dentifrices for 2 min and viable CFUs were enumerated. Exposure to the SEC-xylitol dentifrice resulted in a significant reduction in bacterial viability, which was greater than that shown by the CHX dentifrice, against all organisms tested. The SEC-xylitol dentifrice also exhibited greater antimicrobial activity against all organsims in well diffusion assays compared to CHX. Dentifrice activity was also evaluated against a three species community of Strep. gordonii, Strep. mutans, and Coryne. matruchotii using bacterial live/dead stain. The SEC-xylitol dentifrice was at least as effective as CHX in removal of the multispecies community. The combination of SEC and xylitol generates a highly effective antimicrobial dentifrice with greater antibacterial activity than a standard 0.12% CHX formulations. SEC and xylitol combinations are worthy of further investigation for routine use and in the management of gingivitis and periodontal disease.
PUBLISHED
Keywords: Streptococcus mutans; Antimicrobial; Chlorhexidine; Dentifrice; Enzyme; Xylitol